In vitro recellularization and characterization of sheep pulmonary valves after decellularization for preclinical studies - Inal, Muesluem Suleyman; Darcan, Cihan; Akpek, Ali (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2025)
Decellularized grafts have shown promising results in tissue engineering. The aim of decellularization is to create as caffold that is devoid of immunogenic components, has natural tissue architecture, and can provide cellularity again. The aim of our study is to obtain a living/regenerative valve by coculture of HUVEC and human dermal fibroblast cells on the pulmonary heart valves of decellularized young sheep and subsequently perform their in vitro characterization to determine its suitability for clinical studies. Various characterization tests were applied to sheep pulmonary heart valves decellularized by the detergent-based method. HUVEC and dermal fibroblast cells were seeded on the scaffold, and their viability was determined by MTT analysis, adhesion by SEM, and cell infiltration by histological staining. Finally, to determine the regenerative ability of the resulting live cap, collagen type I (Col1), collagen type III (Col3), and elastin(Eln) gene expressions were analyzed by PCR. The results showed that cell proliferation increased day by day on the scaffold. In histological findings, it was observed that cellular regeneration was almost completely achieved, especially in arterial wall samples. According to PCR findings, a significant increase in Col1, Col3, and Eln gene expressions was observed in arterial wall samples. In this study, for the first time in the literature, the regeneration potential of differentiated human cells on decellularized sheep heart valves was observed, and markers related to new ECM production were analyzed. In conclusion, we suggest that the decellularized heart valves of young sheep can be used as a starting matrix in tissue engineering studies, and clinical studies are needed.
Keywords: Tissue engineering; pulmonary valve; decellularization; xenograft, regeneration; biomaterial; HEART-VALVE; PERFORMANCE; CONDUITS; REPLACEMENT; Engineering